MODERN ASPECTS OF DIAGNOSIS OF ACUTE AND CHRONIC PROSTATITIS - Isomadinova Lola Kamoliddinovna; Rahmonov Husan (Web of Journals Publishing, 2024)
Prostatitis is one of the most common urological conditions affecting men. According to medical statistics, up to 50% of men over the age of 50 experience symptoms of prostatitis at some point in their lives. This condition significantly reduces the quality of life by causing chronic pain, urinary problems, and sexual dysfunction. Additionally, it can lead to serious complications, including infertility and impaired sexual function. Therefore, developing effective diagnostic methods for prostatitis is a crucial task in contemporary medicine.
Keywords: Prostatitis, chronic pain, urinary problems, sexual dysfunction.